Entrepreneurial intensity, capability and external environmental influences in state-owned agencies, entities and components in the Gauteng Province, South Africa - Mgwenya, John July (My University, 2023)
The raging debate on the extent of entrepreneurship within the public sector environment is not abating. There is a school of thought which contends that a version of public sector entrepreneurship (PSE) is possible within the confines of government regulatory regime. With this in mind, the aim of the research was to investigate corporate entrepreneurship by examining how the influence of entrepreneurial intensity and capability at the organisational level influence performance, while at the same time considering external influences (e.g. legislation) on this relationship (www.sajems.org). The scope of the study was limited to 6 state-owned entities under the jurisdiction of the Gauteng Provincial Government. The study used empirical and quantitative research, and the research approach adopted in this study is deductive, using self-administered structured questionnaires to a selected sample of respondents. Correlational and regression analyses were employed to test the hypotheses. The research found that entrepreneurial intensity and capabilities do influence organisational performance in various degrees in the state-owned entities in the Gauteng provincial government jurisdiction. The findings provide valuable insights into topic of entrepreneurship as they relate to the South African public sector context. There is a need for mindset shift to embrace technological distinctiveness to achieve competitive advantage as means of differentiating products and services in relation to competitors. On a conceptual and theoretical level, the study will contribute towards more clarity on the role of entrepreneurial intensity and capability within established state-owned entities. The empirical (or practical) application of new insights may inherently influence the policy directives of SOEs and entities within the Gauteng province and beyond.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Entrepreneurial orientation; Risk-taking; Legislative compliance; SDG-8: Decent work and economic growth